Electrocatalytic Oxidation and Determination of Hydrogen Peroxide at Poly(N-methylthionine) Electrodes. Issue 9 (1st January 2015) - Chen, Chuanxiang; Hong, Xiaozhang; Xu, Tingting; Chen, Ankang; Lu, Lin; Gao, Yuhua
Abstract : Poly( N -methylthionine) (PNMTh) was utilized as an electrocatalyst to lower the overpotential of hydrogen peroxide (H2 O2 ) oxidation compared with bulk platinum. The electrocatalyst was prepared by potential cycling from a phosphate buffer solution containing N -methylthionine and sodium chloride on a platinum foil electrode. X-ray photoelectron spectroscopy (XPS) demonstrated the formation of the polymer film. Cyclic voltammetry and chronoamperometry showed the PNMTh electrode had an excellent electrocatalytic activity toward H2 O2 oxidation. Furthermore, the PNMTh electrode was found to be promising as an amperometric detector for H2 O2 . The proposed enzyme-free H2 O2 sensor exhibited a wide linear range (1–700 μM), fast response (2 s), low detection limit (0.12 μM), high sensitivity, and long-term stability, plus low cost.